2009
DOI: 10.1038/mt.2009.88
|View full text |Cite
|
Sign up to set email alerts
|

AAV2/8-mediated Correction of OTC Deficiency Is Robust in Adult but Not Neonatal Spfash Mice

Abstract: Ornithine transcarbamylase (OTC) deficiency, the most common urea cycle disorder, is associated with severe hyperammonemia accompanied by a high risk of neurological damage and death in patients presenting with the neonatal-onset form. Contemporary therapies, including liver transplantation, remain inadequate with considerable morbidity, justifying vigorous investigation of alternate therapies. Clinical evidence suggests that as little as 3% normal enzyme activity is sufficient to ameliorate the severe neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
105
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 33 publications
4
105
0
Order By: Relevance
“…Importantly, this confirmed that the vectors encoded stable OTC proteins that were successfully targeted to the liver. Consistent with our earlier findings, 6 the mutant OTC expression levels achieved were markedly in excess of endogenous physiological wild-type OTC levels.…”
Section: Introduction Results and Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Importantly, this confirmed that the vectors encoded stable OTC proteins that were successfully targeted to the liver. Consistent with our earlier findings, 6 the mutant OTC expression levels achieved were markedly in excess of endogenous physiological wild-type OTC levels.…”
Section: Introduction Results and Discussionsupporting
confidence: 92%
“…The level of urinary orotic acid in affected adult mice is significantly higher at 629 ± 70 mmol orotate per mmol creatinine (n ¼ 8). 6 This implies that these mutant proteins do not exert a phenotypically significant dominant-negative effect on wild-type OTC.…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations